Palliative care: A positive outcome for cancer patients? - JE Maree (AOSIS, 2008)
The development of palliative care in terms of recognizing the needs of the dying, palliative care becoming a nursing and medical speciality, the involvement of the World Health Organization in palliative care and the continuous development of treatment modalities available to cancer patients creates the expectation that the outcomes for the patient should also be positively influenced. The purpose of the study was to determine the most common symptoms of advanced cancer patients treated in a public and private hospital in Tshwane, and whether advances in palliative care improved the outcomes for these patients by decreasing the prevalence of symptoms experienced. The design of the study was a quantitative survey. The population consisted of patients with advanced cancer receiving palliative treatment as out patients in radiation and medical oncology clinics in a public and private hospital the Tshwane Metropolitan area. The sampling method was convenient and the sample size was 148 participants (n=148). Data was gathered by means of an interview and self report. Data analysis was done by means of descriptive statistics. The results of the study indicated that a high number of patients still experience problems that could have been prevented. Pain was found to be the biggest problem for patients (76.4%) followed by weakness and fatigue (65.5%), nausea and vomiting (65.5%) and a dry mouth (46.6%). Thirst was reported by 41.2% of the sample. The study provides evidence that the development of palliative care did not have a positive outcome for patients by reducing the prevalence of symptoms experienced.